Understand the reality of trade wars between the United States and China - Setiawan, Rizky Bintang; Mustafa, (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores the US and Chinese trade war. We focus on the reality on the background of the war and compare with past trade. The US suggests that they are a victim of exploitation by China, even though US are a world economic power. However, US argue that other countries have wong estimation in evaluation the current US economic realities. The real reason that caused the dispute between the US and Chinese will be discussed in this paper.